Decoding of polar-coded OFDM systems over multipath fading channels with interleaving and channel state information - Mingbao Wu; Yi Yu; Fangying Wan; Yanhua Lin; Yong Li; Zhian Zheng (Scientific Reports, 2024)
Abstract In this paper, we investigate the decoding performance and corresponding decoding strategies for polar-coded orthogonal frequency division multiplexing (OFDM) system operating under multipath fading channels. Multipath fading channels lead to frequency selective fading of the OFDM signal, resulting in varying levels of noise interference across different subcarriers after equalization. Furthermore, frequency selective fading induces burst errors in the equalized information, thereby significantly degrading the decoding performance. To address these issues, we propose two schemes in this paper to enhance the decoding performance of polar-coded OFDM system. Firstly, we integrate the channel state information of each subcarrier into the generation of soft information for the polar codes decoder, in order to alleviate the degradation of decoding performance caused by variations in signal-to-noise ratio across subcarriers during OFDM demodulation. Secondly, we introduce a packet interleaving design after the polar codes encoder to enhance the robustness of polar codes against burst errors. Simulation results demonstrate that the combined application of these two decoding strategies significantly outperforms the conventional scheme in terms of transmission performance over multipath fading channels. The findings of this study suggest that, within the context of future wireless communication systems utilizing Polar-OFDM, the concurrent implementation of our two proposed decoding strategies is essential for achieving robust error correction performance in the OFDM system.